ANALISIS HUKUM TERHADAP PERLINDUNGAN DATA PRIBADI DALAM KONTEKS PENGUNAAN TEKNOLOGI BIG DATA (Perspektif Perlindungan dan Kemanan Data Pribadi) - Putra, Ridwan; Hayati, Nandie; Maizen, Safi’i; Okta Sari, Feby (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Indonesia is a state of law, States are obliged to provide protection of the right to personal data stems from the right of respect for private life. The concept of personal life refers to man as a living being. The individual is the primary holder of the right to protect personal data, there are categories of legal bodies that need to be regulated in relation to the protection of personal data. One legal body is the personal data controller i.e. human beings as subjects, public or private legal entities and other social organizations that individually or collectively control personal information. Protecting personal data in the digital age requires comprehensive regulation. The establishment of a special body is necessary to monitor and protect personal data from misuse. The legal protection of personal data in the use of big data technology must follow the rapid development of technology in order to be able to resolve the data leakage that occurs especially in the sphere of government. A lot of data leaks happen on personal data. Governments should play an active role in enforcing proper regulation and raising awareness of data protection rights, as well as monitoring and enforcement of the law against data theft.Keywords: Protection, Personal Data, Technology Uses, Big Data